2021
DOI: 10.3389/fphar.2021.694107
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Ameliorates Symptoms of High-Fat Diet-Fed Mice by Reversing Imbalanced Gut Microbiota

Abstract: Glucosamine (GlcN) is used as a supplement for arthritis and joint pain and has been proved to have effects on inflammation, cancer, and cardiovascular diseases. However, there are limited studies on the regulatory mechanism of GlcN against glucose and lipid metabolism disorder. In this study, we treated high-fat diet (HFD)-induced diabetic mice with GlcN (1 mg/ml, in drinking water) for five months. The results show that GlcN significantly reduced the fasting blood glucose of HFD-fed mice and improved glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[1]. For example, T2DM, hyperlipidemia and intestinal imbalance are typical complications of GLMD [18][19][20]. HTC water extract could signi cantly improve the abnormal blood sugar, lipid accumulation, and gut microbiome in GLMD rats.…”
Section: Discussionmentioning
confidence: 99%
“…[1]. For example, T2DM, hyperlipidemia and intestinal imbalance are typical complications of GLMD [18][19][20]. HTC water extract could signi cantly improve the abnormal blood sugar, lipid accumulation, and gut microbiome in GLMD rats.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, not all lipid profiles would be affected in our findings, which indicated that there might be particular pathways through which TMP decreased the plasma lipid level. Most lipids are metabolized in the liver and adipose tissue [ 30 ]. The SREBP and its escort protein SCAP are involved in cholesterol biosynthesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As relative fecal and cecal abundances of Blautia have been related to increased serum concentrations of glucose and insulin in pigs [ 30 ], low levels of this genus may be associated with beneficial effects. In support of this possibility, elevated populations of Blautia have been recorded in mice fed a high-fat diet showing impaired glucose tolerance [ 31 ]. In humans, fecal Blautia has been inversely associated with visceral fat area [ 32 ].…”
Section: Discussionmentioning
confidence: 99%